Mechanical Behaviour of the Porous and Foam Aluminium in Conditions of Compression: Determination of Key Mechanical Characteristics - Byakova, O.V.; Vlasov, A.O.; Semenov, M.V.; Zatsarna, O.V.; Gnyloskurenko, S.V. (Металлофизика и новейшие технологии, 2017)
The paper emphasizes harmonized recommendations for mechanical tests of highly-porous aluminium and aluminium foam to be applicable for analysing their compression response under quasi-static loading as well as determining reliable and reproducible results essentially required for practice problems of engineering design.